Clinical remission rate and drug withdrawal status in articular juvenile idiopathic arthritis - Akira Oshima; Takasuke Ebato; Masanori Kaneko; Yoshiaki Shikama; Tomoyuki Imagawa (Pediatric Rheumatology Online Journal)
Abstract Background The clinical remission rate of articular juvenile idiopathic arthritis (JIA) differs according to the disease categories. At present, there is no consensus regarding drug withdrawal after remission is achieved. Objectives To clarify the clinical remission rate and drug withdrawal status of patients with juvenile idiopathic arthritis (JIA). Methods We conducted a retrospective observational study in patients who developed articular JIA by 2017 and were followed up (2013–2022). The Wallace criteria were used as remission criteria. Results Forty-nine patients were included, i.e., 16 (33%) with polyarticular JIA (PJIA) and 33 (67%) with oligoarticular JIA (OJIA). Rheumatoid factor-positive (RF +) PJIA had significantly higher biological disease-modifying antirheumatic drug (bDMARD) introduction rates (86%, p < 0.01). The rate of clinical remission off medication was significantly higher in OJIA (67%). Numerous cases of RF + PJIA (50%), RF-negative (RF −) PJIA (25%), and OJIA (30%) flared within 2 years after conventional synthetic disease-modifying antirheumatic drug withdrawal. Patients with RF − PJIA and OJIA (two cases each) discontinued bDMARDs. Both RF − PJIA cases (100%) and half of OJIA cases (50%) flared within 2 years after bDMARD withdrawal. In one case of OJIA, remission was maintained after withdrawal of all drugs. Conclusions OJIA had the highest rate of clinical remission off medication (67%) versus others. In OJIA, it was possible to discontinue all drugs in some patients with OJIA receiving bDMARDs. In PJIA requiring bDMARDs, withdrawal of bDMARDs was difficult all two cases.